Combining power electronic converters and automation to simulate solar PV systems - Cordeiro, Armando (2022)
This paper presents a solar photovoltaic panel simulator system with the ability to perform automatic tests in different condition according to manufacture parameters. This simulator is based on three buck-boost DC-DC converters controlled by a microcontroller and supported by a Programmable Logic Controller which is responsible for the automatic tests. This solution will allow to achieve fast response, like suddenly changes in the irradiation, temperature, or load. To control the power converter, it will be used a fast and robust sliding mode controller. Therefore, with the proposed system is possible to perform the I-V curve simulation of a solar PV panel, evaluate different MPPT algorithms considering different meteorological and load variation. The main advantage of this work is the possibility to evaluate and test several MPPT algorithms and understand the operation and typical operation of solar PV panels in different conditions. Several simulations and experimental results from a laboratory prototype are presented to confirm the theoretical operation.